2014
DOI: 10.18632/genesandcancer.42
|View full text |Cite
|
Sign up to set email alerts
|

The Bcl-2 inhibitor Obatoclax overcomes resistance to histone deacetylase inhibitors SAHA and LBH589 as radiosensitizers in patient-derived glioblastoma stem-like cells

Abstract: Glioblastoma has shown resistance to histone deacetylase inhibitors (HDACi) as radiosensitizers in cultures with Bcl-XL over-expression. We study the efficacy of SAHA/RTx and LBH589/RTx when manipulating Bcl-2 family proteins using the Bcl-2 inhibitor Obatoclax in patient-derived glioblastoma stem-like cell (GSC) cultures. GSC cultures in general have a deletion in phosphatase and tensin homolog (PTEN). Synergy was determined by the Chou Talalay method. The effects on apoptosis and autophagy were studied by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…[ 20 ]The mRNA of the parental glioblastoma tissue of the GSCs was isolated with the RNeasy Mini kit (#74104, Qiagen Inc., CA, USA) The expression levels were analyzed by the HumanHT-12 v4 Expression BeadChip microarray (Illumina, CA, USA), as we have described previously. [ 21 ] The normalization and batch effect removal was done as described previously by using Partek software, version 6.6 (Partek Inc., St. Louis, MO, USA). The expression data was used to subtype the tumors to the transcriptionally-defined glioblastoma classification of the TCGA.…”
Section: Methodsmentioning
confidence: 99%
“…[ 20 ]The mRNA of the parental glioblastoma tissue of the GSCs was isolated with the RNeasy Mini kit (#74104, Qiagen Inc., CA, USA) The expression levels were analyzed by the HumanHT-12 v4 Expression BeadChip microarray (Illumina, CA, USA), as we have described previously. [ 21 ] The normalization and batch effect removal was done as described previously by using Partek software, version 6.6 (Partek Inc., St. Louis, MO, USA). The expression data was used to subtype the tumors to the transcriptionally-defined glioblastoma classification of the TCGA.…”
Section: Methodsmentioning
confidence: 99%
“…The results have been mostly disappointing, since increased toxicity with cetuximab was not accompanied by improved overall survival compared to standard therapy. Thus cetuximab in combination with radiation has only received FDA approval for the treatment of locally advanced head and neck cancer [ 93 ]. Next generation EGFR inhibitors must prove a better toxicity profile and increased radiosensitivity.…”
Section: Targets For Radiosensitizationmentioning
confidence: 99%
“…Obatoclax, a pan-Bcl-2 inhibitor with promising efficacy, was recently shown by Berghauser et al 99 to overcome apoptosis resistance to the histone deacetylase inhibitors SAHA and LBH589, and to act as a radiosensitizer in patient-derived GSCs. Obatoclax had a synergistic effect with SAHA and LBH589 and sensitizes cells to HDACi/radiation therapy (RTx).…”
Section: Drugs Known To Increase Apoptosis In Cancer Stem Cellsmentioning
confidence: 99%
“…The authors found that the gene predictive for treatment response is the F-box/WD repeat-containing protein-7, which is related to Bcl-2 inhibition and HDACi sensitivity. 99 …”
Section: Drugs Known To Increase Apoptosis In Cancer Stem Cellsmentioning
confidence: 99%